Einige Eigenschaften der Funktionen, die Keine Nullgleiche Dividierte Differenz Besitzen - Kirjacky, E. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Э. Кирьяцкий. Некоторые свойства функций с отличной от нуля разделенной разностьюE. Kirjackis. Funkcijų, kurių padalytas skirtumas nėra lygus nuliui, kai kurios savybės